Training nurses in contraceptive implant procedures: implications for practice in Australia. Issue 1 (February 2021) - Botfield, Jessica R.; Wright, Sarah M.; Fenwick, Sarah E.; Cheng, Yan
ABSTRACT: Background: The contraceptive implant is a long-acting, effective method of contraception. Low uptake in Australia may be partially due to limited clinicians trained in implant procedures. Internationally, nurse-led implant procedures are accepted practice; however, this is not common in Australia. Aim: An evaluation was undertaken to determine the effectiveness of implant training for nurses and consider the implications for clinical service delivery. Methods: Participating nurses (n = 5) completed pre- and post-training surveys, and three were subsequently interviewed. Supervising doctors and nurses (n = 5) were also interviewed. A file audit was conducted to review implant procedures undertaken post-training. Findings: Nurses undertook implant training to acquire new skills and meet patient demand. After the training, all nurses self-reported feeling 'very confident' in inserting the implant and at least 'a little confident' in removing the implant; the latter had minimal impact on removal success, as indicated in the file audit. Overall, nurses and supervising doctors and nurses felt that nurses could play a greater role in the provision of contraceptive implant procedures in Australia. Discussion: Nurse-led procedures would increase access to the contraceptive implant for women, and have a positive impact on service delivery in different healthcare settings; however, funding constraints for nurses remain a significant barrier. Conclusion: Nurses are well placed to undertake contraceptive implant procedures. This would increase access to this method of contraception for women. These findings may inform models of care that promote nurse-led contraceptive procedures in Australia.